KAJIAN METODE KOAGULASI PADA PENGOLAHAN AIR SUMUR MENGANDUNG TIMBAL BERVALENSI II DI KOTA PASURUAN - Esthi Kusdarini (Jurnal IPTEK, 2016)
One of the major needs in human life is water. The quality of water used will reflect the quality of human life. One of the water sources used by local people in Pasuruan is spring water. Spring water is not only used for bathing and washing, but also it used for cooking and drinking for few people. Based on the previous studies, it is known that five samples of spring water are located in densely populated areas containing Pb metal above the maximum limit allowed by the Regulation of the Minister of Health No. 416 / Menkes / Per / IX / 1990. One of simple method that can reduce the content of Pb metal in water is coagulation. The purposes of this research are: 1) to get some kinds of coagulants which could reduce Pb metal content in spring water; 2) to obtain a coagulant efficiency that have been studied in lower levels of Pb in water; 3) to recommend coagulant which can be used to process five samples of spring water containing Pb. This research was using quantitative descriptive technique by collecting data from the study of literature. The research is done in four stages: 1) looked for the laboraturium analysis result of spring water samples from previous studies; 2) compared the results of analysis on the condition of water based on the Regulation of the Minister of Health No. 416 / Menkes / Per / IX / 1990; 3) sought some kinds of coagulant that can be used to reduce the content of Pb in water; 4) assessed the efficiency of coagulants that have been examined by previous studies. The results showed that: 1) the coagulants that can be used to reduce the content of Pb are: a) sea water; b) Moringa seed powder; c) powdered activated hyacinth 2%; d) alum 20 mg / L and 1250 mg / L; e) FeCl3; 2) the efficiency of coagulant sea water reached 95.5%, Moringa seed powder reaches 95.6%, powder activated hyacinth reached 96%; alum 20 mg / L reached 36%, alum 1250 mg / L at 67%; FeCl3 reached 84%; 3) to coagulants that can be used to process five sample wells is seawater, Moringa seed powder, powdered activated hyacinth 2% NaOH, and FeCl3 1000 mg / L.